PERKEMBANGAN PASAR PAGI TANJUNG AUR KOTA PADANG TAHUN 2010-2020 - Rike Maiyusa; Zul Asri (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research discusses the Tanjung Aur Morning Market which is one of the traditional markets in the city of Padang from 2010-2020. The purpose of this study is to reveal the development of the Tanjung Aur Morning Market from 2010-2020. This research includes qualitative research, using historical methods in the form of library studies, archives, and interviews. The traditional market is a space for subsistence commodity transactions whose process is still thick and colored by the atmosphere of the rural economy with strong traditions. From the discussion it can be seen that first, the Tanjung Aur Morning Market is a traditional market that sells daily necessities such as rice, vegetables, fish and clothing. Therefore the Tanjung Aur Morning Market is one of the traditional markets in the city of Padang. Through this research, we can find out market development, market management, types of merchandise and fees for the Tanjung Aur Morning Market. The existence of the Tanjung Aur Morning Market also has an impact on the economy of the surrounding community and the creation of new jobs for the people around the Tanjung Aur Morning Market.Â The Tanjung Aur Morning Market was first established in 2010, when there were only a few traders selling by opening small stalls to place their wares from year to year. This market is growing, and the land owner is asking for permission from the Balai Gadang Village so that he can build small, neatly arranged stalls for rent to traders to sell, so that in 2020 this market will become the main place for buying and selling transactions and a place for traders to sell. The traders only come from areas around Balai Gadang Village. There are also some traders who make their own places using simple materials, such as wood and bamboo, to sell.